A narrative study on work place based conflicts in obstetrics & gynecology department - Khadija Waheed; Mohamed Al-Eraky; Noor-i-kiran Naeem; Sara Ejaz; Amna Khanum (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To explore the patterns in research and underlying factors of conflicts in obstetrics and gynaecology and its effect on restricting the quality of education and training of residents. Methods: The narrative study was conducted at the Obstetrics and Gynaecology Department, Lady Aitchison Hospital, King Edward Medical University, Lahore, Pakistan, from October 2018 to January 2019, and comprised narrative essays by residents associated with the department. Data was subjected to thematic analysis. Results: Of the 27 residents, 26(96.3%) were females and 1(3.7%) was male. Overall, 19(70.3%) were aged 25-30 years and 8(29.6%) were aged 30-35 years. Three levels of conflict were identified: organisational, interpersonal and individual. Causes of organisational conflict included inadequate facilities, poor security and unclear duty appointments. Interpersonal factors included lack of communication, lack of patient autonomy, non-cooperative co-workers, illiteracy of attendants and unprofessional behaviour. Individual factors were overburdening duty hours and duty negligence. Continuous...